Experimental Evaluation of A Cylinder Actuator Control Using McKibben Muscle - Mhd Yusoff, Mohd Akmal; mohd Faudzi, Ahmad 'Athif; Sayahkarajy, Mostafa (International Journal of Integrated Engineering, 2019)
There has been an increased interest in applying pneumatic muscle actuator (PMA) in robotic systems because of its low weight and high compliant characteristics. On the other hand, pneumatic muscle actuator (PMA) is gaining attention in robotic applications because of its low weight and high compliant characteristics. It is known that the McKibben muscle is different from the fluidic cylinder actuator in that the cylinder was unstable in its position and in its velocity in an open-loop system unlike the McKibben that is stable in its position. The modeling and control of McKibben muscle as the actuator for the cylinder are crucial because it is known to have non-linear response, hysteresis and small stroke. In this project, a single acting cylinder model which would have uncontrolled extension to push direction by compressed air, is actuated and controlled using a PMA. The system is designed with two 1.3mm-diameter McKibben muscles attached to the cylinder. Open loop control was used and the result shows that the PMA is able to control the cylinder with good performance.